A Ligand‐Doped Silver Triazolate MOF on the Removal of Diclofenac Sodium via Anion Exchange. Issue 38 (13th October 2020) - Miao, Huixia; Hou, Hongwei; Zhang, Wenhua; Yang, Guang
Abstract: A ligand‐doped silver triazolate MOF[Ag8 (Ph2 tz)5.6 ( t Bu2 tz)0.4 ](BF4 )2 (H2 O)6 (AgTz‐1/2, Ph2 tzH=3, 5‐di‐phenyl‐1, 2, 4‐triazole; t Bu2 tzH=3, 5‐di‐tert‐butyl‐1, 2, 4‐triazole), was successfully synthesized by the use of solid solution approach and characterized by different techniques. The obtained material featuring good thermal and chemical stability is isostrutural with an earlier reported MOF [Ag8 (Ph2 tz)6 ](BF4 )2 (H2 O)3 (AgTz‐1 ). The study on the diclofenac sodium (DCF) adsorption from water by AgTz‐1/2 at higher pH value (pH=10) shows better efficiency in comparison with the parent MOF AgTz‐1 . Especially, using AgTz‐1/2 as the adsorbent, the adsorption capacity at low concentration as well as the reaction rate is remarkable among those reported traditional and MOF materials. Anion‐exchange between BF4 − and anionic DCF play a vital role on the adsorption. More importantly, the used AgTz‐1/2 adsorbent can be well regenerated and reused for the next four cycles of DCF adsorption while maintaining the structural integrity and the removal efficiency. Abstract : A ligand‐doped silver triazolate MOF [Ag8 (Ph2 tz)5.6 ( t Bu2 tz)0.4 ](BF4 )2 (H2 O)6 (AgTz‐1/2) was successfully synthesized and demonstrated better efficiency on the adsorptive removal of diclofenac sodium from water at higher pH value (pH 10) in comparison with the non‐doped parent MOF. The adsorption capacity at low concentration as well as the reaction rate is remarkable among those reported traditional and MOF materials.